Taste your way across the globe: a systematic review of gastronomy tourism literature (2000-2021) - Yong, Rachel Yuen May; Chua, Bee-Lia; Han, Heesup; Kim, Bona (Taylor and Francis Group, 2022)
Gastronomy tourism is a critical driver of regional economic development and socio-cultural renaissance. It has been advocated as part of the tourism recovery initiatives in regards to boosting the worldwide economy in the wake of the COVID-19 pandemic. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol, 397 empirical articles from leading hospitality and tourism journals were systematically examined. This review brought attention to significant developments by using a combination of descriptive analysis, conceptual framework, and topic modeling. Several salient literature gaps and future research directions were amalgamated by utilizing the theory, context, characteristics, and methodology (TCCM) framework.